Effect of LowLevel Laser Therapy on Pain and Functional activity in Patient with Chronic Compression of the Dorsal Root Ganglion: A randomized control trial - Abu el Hagag, Nabil Hassan Ahmed; Ahmed, Osama Fekry; Balbaa, Alaa Eldin Abdel Hakim; Hegazy, Ahmed Abdel El Aziz; El Khozamy., Hamed Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Damage to or irritation of the Dorsal Root Ganglion can lead to intractable symptoms of neuropathic pain that do not respond to typical treatments. This can lead to additional complications in the form of impairment in functioning for the individual .this study was the first study which used the non invasive technique modalities, it was designed and conducted in kasr el ini hospital Cairo university from may 2017 to may 2019, to evaluate and compare between the effect of (LLLT), (TENS) and (US) therapy related to pain relief, range of motion and restoring functional activity for the patients with chronic compression of dorsal root ganglion in retrospective comparative study. a total number of 40 patients suffer from pain related to chronic compression of dorsal root ganglion in the lumbar region for more 3 months, their ages ranged from(40-65) years, They were randomly assigned in forth equal groups with (10) patients in each group. All were received therapeutic exercises for one month three times per week day after other day (12 sessions) in addition to The first group were received (TENS) frequencies from (10- 20 HZ) according the individual sensation for each patient not more to avoid motor contraction. The second group was received LLLT (GaAs) 808 nm 15 joules .The third group was received LLLT (diode) 632 nm 15 joules. The fourth group was received (US) .The pain severity was assessed by visual analog scale ,range of motions for surrounded joints was evaluated by universal goniometry and improvement in motion and activity daily life was evaluated by patient-specific function scale (PSFS): Fl, F2, and F3. Patient's improvement was followed-up during 1-3 months. The data showed that there was significance difference for Comparison pre and post treatment for each function in each group Pre and post treatment for flexion range, extension range ,leg raising ,standing side bending ,walking ,upstairs: at (P value significant if < 0.05), the study shows significance results for all groups with different modalities at the p value 0.0001. For VAS assessment in the all groups show there was significance difference in pain intensity but there was significance difference in between groups. In comparison between the four modalities of treatment (TENS-LASER1-LASER2-US) results showed that the tens therapy was the best modalities of treatment followed by the laser1 (gallium 808) followed by the laser 2 (diode laser632) followed by the ultrasound modalities. Some cases needed more 12 sittings to achieve full recovery and some cases complained from recurrence of pain after 3 months whose needs for follow up and application more sittings. This results indicate that the non invasive modalities of treatment were used improved the complains from dorsal root ganglion compression.